2017
DOI: 10.1007/s13671-017-0182-9
|View full text |Cite
|
Sign up to set email alerts
|

Omalizumab for Chronic Urticaria: Aftermarket Reports of Efficacy and Side Effects

Abstract: Purpose of Review The purpose of this study was to review real-life studies on effectiveness and safety of omalizumab in chronic urticaria (CU). Recent Findings CU is an itching skin disease characterized by wheals, angioedema, or both (present >6 weeks). Omalizumab is a humanized anti-IgE monoclonal antibody approved for treatment of CU and is becoming one of the main treatment options for antihistamine-resistant CU; however, real-life studies on long-term effectiveness and safety are lacking. Summary We pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Our review is intended to provide a comprehensive, critical, and rigorous synthesis of this body of evidence and to provide an informed opinion on the use of omalizumab across the diverse patient phenotypes affected by CIU/CSU. As a systematic review, it extends and updates the clinical and product reviews and summaries on omalizumab in CIU/CSU published to date [27][28][29][30][31][32][33][34][35][36], and provides guidance to clinicians.…”
Section: Introductionmentioning
confidence: 90%
“…Our review is intended to provide a comprehensive, critical, and rigorous synthesis of this body of evidence and to provide an informed opinion on the use of omalizumab across the diverse patient phenotypes affected by CIU/CSU. As a systematic review, it extends and updates the clinical and product reviews and summaries on omalizumab in CIU/CSU published to date [27][28][29][30][31][32][33][34][35][36], and provides guidance to clinicians.…”
Section: Introductionmentioning
confidence: 90%
“…Clinical trials have shown that treatment with omalizumab is effective on urticaria symptoms and disease‐related quality of life and also reduces the need for additional medication . Out‐of‐trial data have shown that approximately 65% of patients with CSU report complete response to omalizumab, while 25% obtain partial response and around 15% have no or very limited response . However, prospective data on real‐life response to omalizumab in CSU are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10] Out-oftrial data have shown that approximately 65% of patients with CSU report complete response to omalizumab, while 25% obtain partial response and around 15% have no or very limited response. 11 However, prospective data on real-life response to omalizumab in CSU are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Konstantinou et al 62 have reported 3 female patients with a mean age of 56.6. They experienced temporary alopecia, which has been suggested to be a potential side effect of omalizumab 63 . Omalizumab associated anaphylaxis was reported in the XTEND-CIU study in two cases 64 .…”
Section: Omalizumab and Side Effectsmentioning
confidence: 99%